Rhinitis medicamentosa: a nationwide survey of Canadian otolaryngologists - James Fowler; Christopher J. Chin; Emad Massoud (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Rhinitis medicamentosa is a non-allergic form of rhinitis that is typically caused by prolonged use of topical nasal decongestants. This condition commonly affects young adults and treatment is not trivial. We aimed to survey Canadian Otolaryngologists to determine practice patterns and their opinions regarding this under-studied condition. Methods An electronic survey was sent to practicing Otolaryngologists within the Canadian Society of Otolaryngology – Head and Neck Surgery. The survey contained 16 questions pertaining to the diagnosis and treatment of rhinitis medicamentosa, as well as opinions on public and primary care awareness of proper use of nasal decongestants. Results The survey was distributed to 533 Otolaryngologists and 69 surveys were returned (response rate of 13%). Cessation and weaning of decongestant (96%), and intranasal steroids (94%) were the most common methods for treating RM. Intranasal saline rinses (55%) and oral steroids (25%) were also supported by some respondents. For those who recommended cessation/weaning, 61% also concurrently introduced an intranasal steroid during this process. The majority responded that current warnings on nasal decongestants were inadequate (75%), and were not visible enough (79%). Conclusions Rhinitis medicamentosa is a common, and very preventable condition. Although the literature lacks a standardized approach to RM, our survey has shown that many Otolaryngologists diagnose and treat RM in a similar manner. Treatment tends to focus on decongestant cessation, often with concurrent introduction of intranasal steroids. It was felt the warning labels on the topical medications are not currently satisfactory.